Bioherbisida Pra Tumbuh Alang-Alang (Imperata cylindrica) untuk Pengendalian Gulma di Perkebunan Kelapa Sawit - Vira Irma Sari; Sylvia Nanda; Rufinusta Sinuraya (JURNAL CITRA WIDYA EDUKASI, 2017)
Controlling weed using herbicide by continuously would be had negative affect for environment and make weed resistance. This problem must be resolved with more eco-friendly solution, such as using pre-emergence bioherbicide. Bioherbicides are herbicides derived from natural ingredients and contain chemical compounds that capable of controlling weeds, such as Imperata cylindrica, because it is contains allelochemical that inhibit the growth of others plant. The research was arranged in a non factorial randomized design with two replication, which consists of 5 treatments, namely, A0 (control), A1 (herbicide Glyphosate 1%), A2 (bioherbicide extract 1%), A3 (bioherbicide extract 3%), A4 (bioherbicide extract 5%). Data were analyzed using analysis of variance and a further test DMRT (Duncan Multiple Range Test). The results from this study showed that alang-alang (Imperata cylindrica L.) could be alternative bioherbicides for controlling weed in oil palm plantation. Pre-emergence bioherbicides significantly affect the growth of weeds in 7 and 21 days after application. The best bioherbicides concentration is 1%, and its bioherbicides contains of alelochemical is flavonoid.